Modelo de gestión empresarial de los agricultores de la Zona de Intag, Cantón Cotacachi - Aragón, Juan Pablo; Albuja, Marcelo; Burbano, Ena; Sánchez, Franklin; Erazo, Alex; Aragón, Mauricio (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The rural sectors where the main economic activity is agriculture do not always apply technical criteria in the management of their crops, even less in the administration of their resources. Similarly happens with farmers in the Intag area. The lack of technique in the business management of the micro, small, medium and large companies results in an inefficient productive process that affects the economic income and therefore the level of life of the farmers. The present work elaborates a model of business management based on scientific techniques and experience of the farmers that through its implementation will help the producers in the optimization of resources and time. The objectives of the research were to identify the current management model and propose a management model with greater efficiency. The type of research used was descriptive, a qualitative method since it evaluated characteristics of the population with respect to its business management through the technique of the survey. The business management model used today is based on experience and considering economic and climatic aspects. The proposed model is based on administrative functions of planning, organization, management, control, and coordination as a transversal axis. The application of this management model will support the efficient production processes in the Intag area.